Arboreal forage lichens in partial cuts – a synthesis of research results from British Columbia, Canada - Stevenson, Susan K.; Coxson, Darwyn S. (Rangifer, 2007)
The mountain ecotype of the woodland caribou (Rangifer tarandus caribou) is highly dependent on the arboreal hair lichens Bryoria spp. and Alectoria sarmentosa during winter. In parts of British Columbia, partial-cutting silvicultural systems have been used in an effort to provide continuously usable winter habitat for mountain caribou, while allowing some timber removal. We reviewed available information about the changes in hair lichens after partial cutting in Engelmann spruce (Picea engelmannii) – subalpine fir (Abies lasiocarpa) forests of British Columbian and Idaho. Generally, abundance of Bryoria spp. in the lower canopy of individual residual trees increases with increased exposure after partial cutting, until the new regeneration begins to shelter the lower canopy of the residuals. Heavy basal area removal, however, results in low lichen availability at the stand level for many years. Abundance of Bryoria on the regeneration is low, and appears to be limited largely by the structure of the young trees, not by lichen dispersal, although dispersal capability may be limiting in Alectoria. Both distributional and physiological data suggest that Bryoria is intolerant of prolonged wetting, and that increased ventilation, rather than increased light, accounts for enhanced Bryoria abundance in the partial cuts. Alectoria sarmentosa reaches its physiological optimum in the lower canopy of unharvested stands; its growth rates are somewhat reduced in the more exposed environment of partial cuts. Both genera are capable of rapid growth: over a 7-year period, individual thalli of A. sarmentosa and Bryoria spp. (excluding those with a net biomass loss due to fragmentation) in an unlogged stand more than tripled their biomass. Calculated growth rates, as well as dispersal potential, are influenced by fragmentation. Bryoria produces more abundant, but smaller, fragments than Alectoria, and fragmentation in both genera increases in partial cuts. In subalpine mountain caribou habitat, partial-cutting prescriptions that enhance exposure of residual trees while keeping basal area removal low will maintain forage best. Regeneration management should focus on maintaining ventilation in the lower canopy of the residual stand.